Pengembangan Diversifikasi Produk Tiwul Instan untuk Meningkatkan Daya Saing UKM di Kabupaten Wonosobo - Santi Dwi Astuti; Kusmantoro Edi; . Furqon; Indah Nuraeni (Institut Pertanian Bogor, 2019)
Instant tiwul is a major product in Wonosobo District and made from cassava. Cassava tubers from Wonosobo has a delicious taste, low prices, and high crop productivity. The applied methods were technology transfer, supplying production tools and equipment, applying technology and production assistance, and evaluation monitoring. The application of technology and production assistance was carried out for 12 months. The results showed that: 1) Technology transfer programs are able to increase the knowledge, technology, and participants motivation to follow up on the technologies that were introduced, including changing production habits in accordance with guidelines on producing good food for household scale industries; 2) Providing production equipment, instruments and equipment repairs, and arrangements of production room layouts are able to increase the capacity and quality of SMEs’ products; 3) Assistance applying technology and during continuous production of functional instant tiwul and bakery goods based on tiwul flour were able to maintain consistent product quality in accordance with the established standards; 4) Various promotional activities carried out and the marketing methods applied were able to significantly increase the sales and profits of SMEs. Overall, this program was able to increase the knowledge, technology, variety, quality, production capacity, income, and competitiveness of SMEs.